Intensification of antihyperglycemic therapy among patients with incident diabetes: a Surveillance Prevention and Management of Diabetes Mellitus (SUPREME‐DM) study. (18th March 2014) - Raebel, Marsha A.; Ellis, Jennifer L.; Schroeder, Emily B.; Xu, Stanley; O'Connor, Patrick J.; Segal, Jodi B.; Butler, Melissa G.; Schmittdiel, Julie A.; Kirchner, H. Lester; Goodrich, Glenn K.; Lawrence, Jean M.; Nichols, Gregory A.; et al.
ABSTRACT Purpose Antihyperglycemic medication intensification practices among patients with incident diabetes are incompletely understood. We characterized the first intensification the year after oral antihyperglycemic medication initiation among incident diabetes patients. Methods This retrospective cohort study across 11 US health systems included adults identified with incident diabetes between 2005 and 2009 who started oral antihyperglycemic monotherapy or combination therapy within 6 months after diabetes identification. We determined intensification, defined as increased index medication dosage, addition of another oral medication, or switch to/addition of insulin 31–365 days after initial antihyperglycemic dispensing. Cox regression was used to assess intensification for patient, temporal, and system covariates, adjusting for glycosylated hemoglobin (HbA1c) as a time‐dependent variable. Results Among 41 233 patients, 33.5% and 45.3% had treatment intensified within 6 and 12 months, respectively. This first intensification was most often with increased index medication dosage (78%), least often with insulin (<1%). HbA1c% was strongly associated with intensification (adjusted hazard ratios [HR] 1.59, 3.62, 4.44, and 5.52 for HbA1c 6.5% to <7%, 7% to <7.5%, 7.5 to <8%, and ≥8%, respectively, all P < 0.001, compared with HbA1c < 6.5%). In patients initially on monotherapy, age modified the HbA1c effect: at HbA1c < 7%, the HR differed little between middle‐aged and older patients; at HbA1c ≥ 7%, the HR decreased with older age (e.g., age 40–49 years and HbA1c ≥ 8%: HR 8.14; age ≥ 80 years and HbA1c ≥ 8%: HR 4.44; compared with age ≥ 80 years and HbA1c < 6.5%). Within 1 year, 84.3% achieved HbA1c < 8%; 65.1% achieved HbA1c < 7%. Conclusions Clinicians appear to be applying treatment intensification guidelines and individualizing therapy by considering patient age, achieving glycemic control among most incident diabetes patients. Copyright © 2014 John Wiley & Sons, Ltd.